Veliki razvojni projekti in skladni regionalni razvoj - Horvat, Andrej; Hren, Marko; Juvančič, Luka; Nared, Janez; Perko, Drago; Piry, Ivo; Ravbar, Marjan; Rončević, Borut (Regionalni razvoj, 2007)
In order to reduce the development gap separating it from the most developed European countries, Slovenia faces numerous developmental challenges. On the one hand, it is trying to promote competitiveness and innovation to stimulate economic growth, and on the other hand it is using various measures to ensure more even development across its entire territory. In the past, the main efforts focused on effective inclusion in the EU and the Eurozone, whereas now seeking domestic reserves to establish and strengthen Slovenia's position among the most developed countries is at the forefront. This demands an important shift in thinking because achieving developmental goals is no longer in the domain of others or dependent on others, but is the result of Slovenia's own decisions, knowledge, and resourcefulness. This must be taken into account, especially at the beginning of a new program period and when preparing new strategic development documents.